2020
DOI: 10.1029/2020gb006727
|View full text |Cite
|
Sign up to set email alerts
|

Southern Ocean Calcification Controls the Global Distribution of Alkalinity

Abstract: Biological processes in Southern Ocean surface waters have widespread impacts on global productivity and oceanic CO 2 storage. Here, we demonstrate that biological calcification in the Southern Ocean exerts a strong control on the global distribution of alkalinity. The signature of Southern Ocean calcification is evident in observations as a depletion of potential alkalinity within portions of Subantarctic Mode and Intermediate Water. Experiments with an ocean general circulation model indicate that calcificat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 111 publications
2
21
0
Order By: Relevance
“…Sarmiento et al. (2007) demonstrated that the Southern Ocean effectively traps silica (see also Moore et al., 2018; Primeau et al., 2013), a phenomena we have also demonstrated operates in POP for CaCO 3 and alkalinity (Krumhardt, Long, et al., 2020; Krumhardt, Lovenduski, et al., 2020). In this vein, excessive silica leakage from the Southern Ocean in CESM2 may help explain why upper‐ocean SiO 3 concentrations are too high at the surface over much of the rest of the global ocean, with the exception of the North Pacific (Figure 8).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Sarmiento et al. (2007) demonstrated that the Southern Ocean effectively traps silica (see also Moore et al., 2018; Primeau et al., 2013), a phenomena we have also demonstrated operates in POP for CaCO 3 and alkalinity (Krumhardt, Long, et al., 2020; Krumhardt, Lovenduski, et al., 2020). In this vein, excessive silica leakage from the Southern Ocean in CESM2 may help explain why upper‐ocean SiO 3 concentrations are too high at the surface over much of the rest of the global ocean, with the exception of the North Pacific (Figure 8).…”
Section: Resultssupporting
confidence: 63%
“…The CESM‐LE enabled a series of studies that explicitly separated natural variability from anthropogenic forced trends in ocean biogeochemistry (Eddebbar et al., 2019; Krumhardt et al., 2017; Long et al., 2016; Lovenduski et al., 2015, 2016; McKinley et al., 2016). BEC has also been used in Decadal Prediction experiments with CESM1 (Yeager et al., 2012), and a handful of studies have examined predictability of ocean biogeochemical dynamics in this framework (e.g., Krumhardt, Long, et al., 2020; Krumhardt, Lovenduski, et al., 2020; Lovenduski et al., 2019; Yeager et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…By additionally facilitating a more efficient transfer of POM to greater depths via the production of the ballasting agent calcite (see Figures 2b and S5 and e.g., Rosengard et al., 2015), coccolithophores directly contribute to setting the fraction of nitrate trapped in the SO, as opposed to being transported to lower latitudes. Altogether, acknowledging the impact of SO coccolithophores on carbonate chemistry (not assessed here, but see Krumhardt et al., 2020), this suggests that a change in the relative importance of diatoms and coccolithophores directly affects not only the Si‐to‐N ratio of exported waters, but also global carbon cycling.…”
Section: Discussionmentioning
confidence: 54%
“…North of the APF, where diatom growth is limited by silicic acid availability, coccolithophores are more efficient than other similarly sized phytoplankton in drawing down nitrate (Balch et al, 2016;Nissen et al, 2018), thus giving coccolithophores a vital role in setting the transition from negative Si* levels to zero Si* between 30 and  40 E S. By additionally facilitating a more efficient transfer of POM to greater depths via the production of the ballasting agent calcite (see Figures 2b and S5 and e.g., Rosengard et al, 2015), coccolithophores directly contribute to setting the fraction of nitrate trapped in the SO, as opposed to being transported to lower latitudes. Altogether, acknowledging the impact of SO coccolithophores on carbonate chemistry (not assessed here, but see Krumhardt et al, 2020), this suggests that a change in the relative importance of diatoms and coccolithophores directly affects not only the Si-to-N ratio of exported waters, but also global carbon cycling.…”
Section: Discussionmentioning
confidence: 68%
“…Similarly, a minimum in the phase lag between Antarctic temperature and obliquity, and ice volume and obliquity, between 450-350 ka has also been attributed to a 400 kyr forcing of CO2 43 . More intense coccolithophore production in the Sub-Antarctic zone of the Southern Ocean, has been modeled to decrease the buffering capacity of the surface ocean globally and therefore reduce the CO2 uptake capacity of the ocean 44 . Therefore, the strong enhancement of coccolithophore production in the Sub-Antarctic zone which we show between 500-400 ka, should be investigated as a potential additional mechanism for modulation of atmospheric CO2 on long eccentricity periods.…”
Section: Discussionmentioning
confidence: 99%